Nutrition and SDG 11: Healthy diets, nutrition and urban settlements - Garrett, James; Ruel, Marie T. (Bioversity International and the International Center for Tropical Agriculture, 2020)
Good nutrition is integral to human well-being and to humanity’s ability to achieve the Sustainable Development Goals (SDGs). Nutrition permeates almost all the SDGs, both as an outcome as well as an important input into their achievement, especially in terms of strengthening human capital. This paper focuses on the specific relationship of nutrition with SDG11, “Make cities and human settlements inclusive, safe, resilient and sustainable.”